HARAPAN DAN TANTANGAN GURU PEMBELAJAR MODA DARING - Sutrisno Djaja (Economic Education, University of Jember, 2016)
Aan increase in competence of teachers learning is a strategic to reach teachers with a capacity of cruising area that is geographically difficult to reach but having internet access , learning teachers is designed and developed by gtk who expected to use by teachers with indefinite period of time and space ,until the objective can improved that competence .teacher learning can do expected , in the end can improve the quality of education in indonesia .One of learning program for teachers is conducted in online and face-to-face with accompanied by mentor and facilitated by preceptor .Key words : Teachers learner, mode of online